Application of redox titration techniques for analysis of hydrometallurgical solutions - O. Bazhko (The Southern African Institute of Mining and Metallurgy, 2009)
Regular analysis of different streams is important for the control of hydrometallurgical processes. Various physical and physical-chemical methods are applied for this purpose. Many modern methods require costly equipment and are subject to interferences. Therefore, redoxtitration methods remain of interest. The use of different types of oxidizing and reducing agents as well as redox indicators enables many cations and anions to be rapidly and accurately analysed. Sometimes redox titrations require the prior preparation and addition of masking agents. Selective, sensitive and low-cost methods of redoxtitration of copper and SO2 in plant conditions are described.